Comparing Robotic-Assisted Thoracoscopic Surgery (RATS) vs Video-Assisted Thoracoscopic Surgery (VATS) Approaches for Non-Small Cell Lung Cancer (NSCLC): a Systematic Review and Meta-Analysis - Katritama, Arinda Agung; Yasa, Ketut Putu; Tidja, Yonatan Esli Alexander (International Journal Labs, 2023)
Video-assisted thoracoscopic surgery (VATS) has demonstrated its efficacy and improved clinical outcomes as an option for early-stage non-small cell lung cancer. The development of robotic-assisted thoracoscopic surgery (RATS) has become the newest alternative to VATS. This study aims to compare VATS and RATS in terms of clinical outcomes. This Systematic Review research used the PRISMA method. RATS is proven to be an alternative with superior results compared to VATS on the Mortality in 30 days parameter (OR 0.59, 95% CI = 0.40, 0.86, I2 : 0%; p<0.006) and transfusion rate (OR = 0.50; 95% CI: 0.27 - 0.92, I2: 6%; p = 0.34). There was no significant difference between the RATS vs VATS procedure in terms of duration of surgery (OR = 0.50; 95%CI: 0.27 - 0.92), and intraoperative complications (OR 1.98, 95%CI: 0.12 - 32.44) and postoperative complications (OR 1.05, 95%CI: 0.93 - 1.19). The parameters of length of stay and chest drain duration in most of the studies show that VATS requires longer treatment time and thoracic drainage time than RATS. RATS can be an alternative to minimally invasive surgery in early-stage lung cancer with a lower risk of death and transfusion requirements than VATS, but there is no difference in the duration of surgery, as well as intraoperative and postoperative complications.